2007
DOI: 10.1002/aic.11306
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and mass transfer in a draft tube airlift reactor with dilute alcohol solutions

Abstract: in Wiley InterScience (www.interscience.wiley.com).The aim of this work was to investigate an influence of different alcohols on the behavior of a draft tube airlift reactor. The main hydrodynamic and mass transfer parameters in 1 wt % aqueous solutions of five aliphatic alcohols were examined. The results showed that alcohol addition enhanced gas holdup and mass transfer coefficient, but led to notable reduction of liquid velocity and hence elongation of circulation time, relative to the values determined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(118 citation statements)
references
References 29 publications
10
105
1
Order By: Relevance
“…The organic substances (i.e., alcoholic solutions) are repelled from the bubble interface where they adsorb negatively, cause small increase of the surface tension and, finally, inhibit the coalescence [79,80]: the alcohol molecules are composed by hydrophobic and hydrophilic parts that are adsorbed at the interface when dissolved in water, causing the coalescence suppression [81]. Among the literature, some of the relevant studies are here summarized, i.e., Krishna et al [19,20,82] Influence of AR and n* (as defined in Equation (2) on flow regime transition points-data obtained from ref.…”
Section: Influence Of the Liquid Phase Viscositymentioning
confidence: 99%
“…The organic substances (i.e., alcoholic solutions) are repelled from the bubble interface where they adsorb negatively, cause small increase of the surface tension and, finally, inhibit the coalescence [79,80]: the alcohol molecules are composed by hydrophobic and hydrophilic parts that are adsorbed at the interface when dissolved in water, causing the coalescence suppression [81]. Among the literature, some of the relevant studies are here summarized, i.e., Krishna et al [19,20,82] Influence of AR and n* (as defined in Equation (2) on flow regime transition points-data obtained from ref.…”
Section: Influence Of the Liquid Phase Viscositymentioning
confidence: 99%
“…increasing carbon chain length: ethanol > IPA > n-propanol > n-butanol (Sijacki et al, 2009). Hence the greater molecular weight alcohol (in this case IPA) provides a stronger effect on two-phase hydrodynamics (Albijanic et al 2007). Hibiki and Ishii (2002) fitted their void fraction profiles in an OTBC using a power-law equation:…”
Section: (2010)mentioning
confidence: 99%
“…These substances preferentially accumulate at the air-liquid boundary with the hydrophobic part extending towards the centre of the bubble. The monolayer of adsorbed polar molecules makes the interface more rigid; during bubble rise the adsorbed molecules are swept to the rear of the bubble, producing a surface tension gradient, which is balanced by an increased skin friction drag that can reduce the rise velocity and inhibit coalescence (Albijanic et al 2007). Zahradnik et al (1999) studied the effect of n-alcohols on the gas void fraction and concluded that the gas void fraction increased with an increase in the length of the carbon chain, for a given gas superficial velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The main parameter that describes the gas distributor, i.e., initial bubble size, is the orifice diameter (d o ) (Šijački et al, 2011). The influence of alcohols on ε GR and subsequently on W LD , should be linked to changes in the surface tension gradient, i.e., to the coalescence suppression strength of individual alcohols (Albijanić et al, 2007;Camarasa et al, 1999). The effect of hydrodynamic resistance on the liquid velocity in the downcomer depends on the friction coefficient (K f ) in the ELAR and ELAMR, in both operating modes.…”
Section: Correlations Empirical Power Law Correlationsmentioning
confidence: 99%